Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2380084419844937
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PGLYRP1 and TREM-1 during Progression and Resolution of Gingival Inflammation

Abstract: Introduction: The triggering receptor expressed on myeloid cells 1 (TREM-1) signaling pathway is stimulated by bacteria and, together with its putative ligand peptidoglycan recognition protein 1 (PGLYRP1), propagates proinflammatory responses. Objectives: We aimed to evaluate the TREM-1/PGLYRP1/interleukin (IL)–1β regulation in response to biofilm accumulation and removal in an experimental human gingivitis model. Methods: The study (n = 42 participants, mean age: 23.8 ± 3.7 y) comprised a recruitment step (da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Although the main, physiological functions of PGLYRP1 are still ambiguous, PGLYRP1 can be induced in response to systemic infection (Osanai et al, ). Recent work by Silbereisen et al demonstrated that the levels of PGLYRP1 were upregulated in saliva in response to experimental dental plaque accumulation (Silbereisen et al, ). Although PGLYRP1 has antibacterial activities against gram‐positive bacteria, the linking of salivary or serum PGLYRP1 to systemic infection episodes during HD was not previously demonstrated (Lu et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the main, physiological functions of PGLYRP1 are still ambiguous, PGLYRP1 can be induced in response to systemic infection (Osanai et al, ). Recent work by Silbereisen et al demonstrated that the levels of PGLYRP1 were upregulated in saliva in response to experimental dental plaque accumulation (Silbereisen et al, ). Although PGLYRP1 has antibacterial activities against gram‐positive bacteria, the linking of salivary or serum PGLYRP1 to systemic infection episodes during HD was not previously demonstrated (Lu et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1, PGLYRP1, and IL-1 are also known to be regulated during gingival inflammation. 22 This fact together with our findings that the periodontal status seemingly does not affect salivary calprotectin levels, might explain why calprotectin did not correlate with TREM-1, PGLYRP1, and IL-1 in systemic health. In CF children, however, PGLYRP1, IL-1 , and calprotectin positively correlated with each other.…”
Section: Discussionmentioning
confidence: 58%
“…Salivary TREM-1, PGLYRP1, calprotectin, and IL-1 levels were analyzed by commercial enzyme-linked immunosorbent assay (ELISA) kits *, †, ‡, § according to the manufacturer's instructions and as described previously. 22 The TREM-1 ELISA kit is detecting both soluble and membrane-bound TREM-1. Briefly, standards and diluted saliva SNs (TREM-1 (1:3), PGLYRP1 (1:60), calprotectin (1:2,000), and IL-1 (1:20)) were applied to pre-coated (capturing antibodies) 96 well plates (Nunc-Immuno MicroWell 96 well solid plates, Sigma) and incubated for 2 hours at room temperature (RT) after washing and blocking the plates.…”
Section: Analysis Of Trem-1 Pglyrp1 Calprotectin Il-1 and Total mentioning
confidence: 99%
“…Differences in analyte levels over time (day 0 to +35) were investigated by Friedman's test, and Dunn's multiple comparisons test was used to compare analyte levels between individual time points. Mixed‐effects multilevel regression analyses were performed using the software STATA 14.2 (StataCorp) to estimate differences in gingival inflammation (MGI) and plaque (TQHPI) over time. p ‐Values < 0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%